The ORCA program system - Neese, Frank (Wiley interdisciplinary reviews. Computational molecular science, 2012)
ORCA is a general‐purpose quantum chemistry program package that features virtually all modern electronic structure methods (density functional theory, many‐body perturbation and coupled cluster theories, and multireference and semiempirical methods). It is designed with the aim of generality, extendibility, efficiency, and user friendliness. Its main field of application is larger molecules, transition metal complexes, and their spectroscopic properties. ORCA uses standard Gaussian basis functions and is fully parallelized. The article provides an overview of its current possibilities and documents its efficiency. © 2011 John Wiley & Sons, Ltd. This article is categorized under: Software > Quantum Chemistry